Engineering Photoswitching Dynamics in 3D Photochromic Metal–Organic Frameworks through a Metal–Organic Polyhedron Design - Jin, Eunji; Bon, Volodymyr; Das, Shubhajit; Wonanke, A. D. Dinga; Etter, Martin; Karlsen, Martin A.; De, Ankita; Bönisch, Nadine; Heine, Thomas; Kaskel, Stefan (Journal of the American Chemical Society, 2025)
Metal–organic polyhedra (MOPs) are versatile supramolecular building blocks for the design of highly porous frameworks by reticular assembly because of their diverse geometries, multiple degrees of freedom regarding functionalization, and accessible metal sites. Lipophilic functionalization is demonstrated to enable the rational assembly and crystallization with photoactive N-donor ligands in an aliphatic solvent to achieve multiaxially aligned photoresponsive diarylethene (DTE) moieties in 3D frameworks (DUT-210(M), M = Cu and Rh) featuring cooperative switchability. Combined experimental and theoretical investigations based on in situ PXRD, UV–vis spectroscopy, and density functional theory calculations demonstrate deliberate kinetic engineering of photoswitchability based on variations in metal–ligand bond strengths. The novel porous frameworks are an important step toward the knowledge-based development of photon-driven motors, actuators, and release systems.